Outcome after type A aortic dissection repair in patients with preoperative cardiac arrest. (November 2019) - Pan, Emily; Wallinder, Andreas; Peterström, Eric; Geirsson, Arnar; Olsson, Christian; Ahlsson, Anders; Fuglsang, Simon; Gunn, Jarmo; Hansson, Emma C.; Hjortdal, Vibeke; Mennander, Ari; Nozohoor, Shahab; et al.
Abstract: Aim of the study: Patients presenting with acute type A aortic dissection (ATAAD) and cardiac arrest before surgery are considered to have very poor prognosis, but limited data is available. We used a large database to evaluate the outcome of ATAAD patients with a cardiac arrest before surgery. Methods: We evaluated 1154 surgically treated ATAAD patients from the Nordic Consortium for Acute Type A Aortic Dissection (NORCAAD) database between 2005 and 2014. Patients with (n = 44, 3.8%) and without preoperative cardiac arrest were compared and variables univariably associated with mortality in the cardiac arrest group were identified. Median follow-up time was 2.7 years (interquartile range 0.5–5.5). Results: Thirty-day mortality in the arrest and non-arrest group was 43.2% and 16.6%, respectively (odds ratio [OR] 3.83, CI 2.06–7.09; P < 0.001). In the nine patients with ongoing cardiopulmonary resuscitation when cardiopulmonary bypass was initiated, five died intraoperatively and one died after 65 days. In patients surviving the operation, stroke was significantly more common in the arrest group (48.4% vs 18.2%; OR 4.21, CI 2.05–8.67; P < 0.001). In total, 50.0% (22/44) of the arrest patients survived to the end of follow-up. Non-survivors in the arrest group more often had DeBakey type I dissection, cardiac tamponade, cardiac malperfusion and higher preoperative serum lactate (all P < 0.05). Conclusions: Early mortality and complications after ATAAD surgery in patients with a preoperative cardiac arrest are high, but mid-term outcome after surviving the initial period is acceptable. Preoperative cardiac arrest should not be considered an absolute contraindication for a surgical ATAAD repair.